Penerapan Model Pembelajaran Make a Match Untuk Meningkatkan Komunikasi Di Kelas VII.1 SMP Negeri 1 Cariu Tahun Pelajaran 2016/2017 - Yuyun Surdiana (Institut Agama Islam Sahid (INAIS) Bogor, 2021)
The learning outcomes of students who have not reached the Minimum Completeness Criteria (KKM) are caused by the inappropriate method or method applied in learning. So that in understanding a learning material students have difficulty. The learning process that still uses the traditional approach to information and communication technology subjects has the potential to cause boredom, boredom and reduce students' interest and motivation in learning, which will ultimately have an impact on student learning outcomes. This classroom action research aims to create a learning atmosphere that is fun, not boring and improves the quality of learning. So that it can increase student activity in learning, invite students to participate and can improve student learning outcomes in Information and Communication Technology lessons. This study uses the Make a Match learning model, where each student is given a card/paper containing questions and answers from the subject matter being studied. After the card is given, each student tries to find a partner according to the content of the question or make the right pair, they will be given pain or a reward. The analysis step is carried out with initial dialogue, planning, action is carried out in two cycles. The results obtained after this research showed an increase in learning outcomes. The percentage increase in the average cycle I = 76 and the average value in the second cycle = 80. Based on the results of this study, it is highly expected that teachers use this learning model to improve student learning outcomes